3D acquisition and stereo-camera calibration by active devices: A unique structured light encoding framework. (April 2020) - Barone, S.; Neri, P.; Paoli, A.; Razionale, A.V.
Highlights: The work describes a unified framework for 3D optical measurements by active devices. Light encoding is integrated with an LCD screen for stereo-camera calibration. Bundle adjustment is used to correct the screen non-planarity. The same light encoding approach is integrated with a projector for 3D scanning. Results are provided with different optical setups to prove the methodology flexibility. Abstract: The use of light encoding techniques is widespread in the field of 3D surface reconstruction. This paper presents a stereo-camera calibration methodology, which integrates structured light encoding with an active digital device. The structured light encoding approach is proposed to unambiguously solve the stereo matching issue for stereo-camera setups. A sequence of vertical and horizontal binary striped patterns, combined with a checkerboard pattern, is displayed by a high-resolution LCD screen, which is used as calibration board. A bundle adjustment technique is adopted to simultaneously adjust both camera parameters and screen geometry, as part of the stereo-camera calibration process, thus taking into account the possible inaccuracies of the digital display. The same structured light approach, with small variants, is projected by a multimedia digital projector to carry out 3D surface reconstruction. The proposed methodology defines a comprehensive framework for the development of a 3D optical scanner, from calibration to 3D acquisition, which has been validated by measuring primitive surfaces and reconstructing free-form shapes with different stereo-camera setups.